Clinicopathological and prognostic factor analyses of primary fallopian tube carcinoma and high-grade serous ovarian cancer: a single-institution retrospective study - Mengyan Tu; Xueyan Gao; Tianchen Guo; Weiguo Lu; Junfen Xu (World Journal of Surgical Oncology)
Abstract Objective This study aimed to evaluate and compare the clinicopathologic features of primary fallopian tubal carcinoma (PFTC) and high-grade serous ovarian cancer (HGSOC) and explore the prognostic factors of these two malignant tumors. Methods Fifty-seven patients diagnosed with PFTC from 2006 to 2015 and 60 patients diagnosed with HGSOC from 2014 to 2015 with complete prognostic information were identified at Women’s Hospital of Zhejiang University. The clinicopathological and surgical data were collected, and the survival of the patients was followed for 5 years after surgery. The Cox proportional risk model was used to analyze the impact on survival. Results For PFTC patients, the mean age was 57 years (range, 35–77 years). The most common clinical manifestations were abnormal vaginal bleeding and/or discharge (61%). A total of 72% of the cases were found at the early stage, and 90% of the tumors were high grade (51 cases). 51% of patients were diagnosed with PFTC before surgery, while the rest were misdiagnosed. Twenty-one patients relapsed. The overall survival (OS) rate was 82%. OS was significantly related to FIGO stage, the preoperative serum CA 125 level, lymphadenectomy, residual tumor size, appendectomy, and the number of cycles of chemotherapy. However, only FIGO stage was an independent prognostic variable for OS. For patients with HGSOC, the OS rate was 67%. OS was significantly related to FIGO stage, residual tumor size, and laterality. However, only residual tumor size was an independent prognostic variable for OS. Conclusions Our study provides important clinicopathologic insights into PFTC and HGSOC. We identified FIGO stage as an independent prognostic factor for PFTC patients and residual tumor size as an independent prognostic factor for HGSOC patients. These findings emphasize the critical role of accurate staging and achieving a residual tumor size of less than 1 cm during surgery. Our research contributes to refining clinical decision-making, supporting the importance of optimal surgical outcomes, and guiding personalized treatment strategies to improve patient prognosis in both PFTC and HGSOC patients.